Gellan gum/tannic acid hydrogels for cartilage repair: the versatile role of tannic acid as green crosslinker conferring antibacterial and anti-inflammatory properties - Francesco Busto; Alessandro C. Scalia; Piergiorgio Gentile; Sofia Toniolo; Stefania Cometa; Stefano Liotino; Andrea Cochis; Piero Mastrorilli; Elvira De Giglio (Carbohydrate Polymer Technologies and Applications)
A novel hydrogel, containing two gellan gums with different acyl content crosslinked with tannic acid and magnesium ions, was proposed as cartilage substitute. In addition to crosslinking, tannic acid was employed as an anti-inflammatory and antioxidant compound. The analytical characterization of the hydrogel revealed that the interaction between carbohydrates and tannic acid consisted of hydrogen bonds. The hydrogel showed satisfactory mechanical performances (compressive Young’s modulus up to 188 ± 12 kPa, and strain at break up to 55.3 ± 1.5 %). The biological results demonstrated that tannic acid-loaded hydrogels were cytocompatible and significantly enhanced the genetic expression of key chondrogenic markers (Collagen type 2 and SRY-Box Transcription Factor 9), showing up-regulation of ∼30- and 14-fold under physiological conditions, and ∼6- and 3-fold under pro-inflammatory conditions of oxidative stress, compared to the unloaded hydrogels. Moreover, the intrinsic ability of tannic acid to bind pro-inflammatory active species under oxidative stress imparted the scaffold with immunomodulatory properties, as shown by the upregulation of the anti-inflammatory genes Interlukin-10 and Interferon-γ. Finally, tannic acid reported bactericidal and anti-biofilm activity, achieving a bacterial load reduction of over 90 % when hydrogels were infected with Staphylococcus aureus. Thus, this research highlights the multiple bioactivity of the gellan gum/tannic acid hydrogel for cartilage regeneration.